RDA coupled with deep sequencing detects somatic SVA-retrotranspositions and mosaicism in the human brain - Möhner, Jonas; Scheuren, Maurice; Woronzow, Valentina; Schumann, Sven; Zischler, Hans (Frontiers in Cell and Developmental Biology, 2023)
Cells of the developing human brain are affected by the progressive acquisition of genetic and epigenetic alterations that have been reported to contribute to somatic mosaicism in the adult brain and are increasingly considered a possible cause of neurogenetic disorders. Recent work uncovered that the copy-paste transposable element (TE) LINE-1 (L1) is mobilized during brain development and thus mobile non-autonomous TEs like AluY and SINE-VNTR-Alu (SVA) families can use L1 activity in trans, leading to de novo insertions that may influence the variability of neural cells at genetic and epigenetic levels. In contrast to SNPs and when considering substitutional sequence evolution, the presence or absence of TEs at orthologous loci represents highly informative clade markers that provide insight into the lineage relationships between neural cells and how the nervous system evolves in health and disease. SVAs as the ‘youngest’ class of hominoid-specific retrotransposons are preferentially found in gene- and GC-rich regions, are thought to differentially co-regulate nearby genes and exhibit a high mobility in the human germline. Therefore, we asked whether this is reflected in the somatic brain and used a subtractive and kinetic enrichment technique called representational difference analysis (RDA) coupled with deep sequencing to compare different brain regions with respect to de novo SVA insertion patterns. As a result, we detected somatic de novo SVA integrations in all human brain regions analysed and the majority of de novo insertions can be attributed to lineages of telencephalon and metencephalon, since most of the examined integrations are unique to the different brain regions under scrutiny. The SVA positions were used as presence/absence markers, forming informative sites that allowed us to create a maximum parsimony phylogeny of brain regions. Our results largely recapitulate generally accepted evodevo-patterns, reveal chromosome-wide rates of de novo SVA reintegration targets and preferences for specific genomic regions, e.g. GC- and TE-rich regions as well as close proximity to genes that tend to fall into neural-specific gene ontology pathways. We conclude that de novo SVA insertions occur in germline and somatic brain cells at similar target regions, suggesting that similar retrotransposition modes are effective in germline and soma.